3D Printed Art Using Bioplastic and Plant Based Resin - Leote, Rosangella [UNESP] (Association for Computing Machinery (ACM), 2023)
This text presents initial results of an ongoing research project, supported by the CNPq Productivity and Research Scholarship, titled 3D Printing Art with Bioplastic.This project is centered on the theme of Art and Sustainability, focusing on the use of plastics in artistic works. It explores various materials that can be used in the production of sculptures, interactive installations, and other forms of poetic expression, printed either entirely or partially in 3D. The aim is to demonstrate that there are ways to print in plastic with minimal environmental impact. At the same time, the research seeks to address the challenges faced by artists working with computational technologies, including 3D printing, to distance themselves, in the short term, from the use of industrially sourced products harmful to nature. In the current phase of this investigation, printing is carried out using Polylactic Acid (PLA) thermoplastic and photosensitive resins, both considered eco-friendly. PLA is plant-based, biodegradable, biocompatible, and fully recyclable, falling into the category of bioplastics. The resins are of two types: a) plant-based and b) water-washable. Laboratory and field research procedures are conducted both in Brazil and abroad, for technical reasons and in collaboration with the University of Seville.
Arte em impressão 3D com biopl stico e resina de plantas
Keywords: 3D printing; Art and sustainability; biomimicry; bioplastic; interactive sculpture; plant-based resin